KARAKTERISTIK FRUIT LEATHER DARI BUAH BIDARA (ZIZIPHUS MAURITIANA) DAN KULIT BUAH NAGA MERAH SERTA RUMPUT LAUT SEBAGAI BAHAN PENGIKAT - Sri Winarti; Ulya Sarofa; Vidya Vianita Wulandari (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Fruit leather is one of the snack foods made from fruits, in the form ofthin sheets with distinctive consistency and taste depending on the typeof fruit used. One of the fruits that can be processed into fruit leatheris the bidara fruit (Ziziphus mauritiana). To improve the texture andcolor of fruit leather, the red dragon fruit peel is added as a source ofpectin and seaweed Eucheuma cottonii as a source of kappacarrageenan because it can form gel well.The purpose of this studywas to determine the effect and get the best combination of treatmentsfrom the propoetion of bidara fruit and red dragon fruit peel and theconcentration of E. cottonii seaweed on the characteristics of fruitleather. This study used a completely randomized design (CRD)factorial pattern of 2 factors, namely the proportion of bidara fruit andred dragon fruit peel (65%:35%; 70%:30%; 75%:25%) and theconcentration of seaweed E. cottonii (0 %; 0.4%; 0.8%; 1.2%) with 2replications. The data obtained was analysis by ANOVA, if thetreatment that had a significant effect was carried out further testingusing the DMRT test. The results showed the best treatment onproportion 65% of bidara fruit and 35% of red dragon fruit peel and1.2% concentration of seaweed, its produced fruit leather withmoisture content of 15.68%; antioxidant activity of 31.80%; vitamin Clevels of 30.78 mg/100 g; anthocyanin of 3.30 mg/100 g; tensilestrength of 1.4130 N; color includes L* of 42.98, a* of 41.26, b* of18.06; organoleptic scoring test includes taste of 3.16 (slightly soursweet), color of 4.92 (red), texture of 2.36 (not soft); and dietary fiberlevels of 4.06%Fruit leather is one of the snack foods made from fruits, in the form ofthin sheets with distinctive consistency and taste depending on the typeof fruit used. One of the fruits that can be processed into fruit leatheris the bidara fruit (Ziziphus mauritiana). To improve the texture andcolor of fruit leather, the red dragon fruit peel is added as a source ofpectin and seaweed Eucheuma cottonii as a source of kappacarrageenan because it can form gel well.The purpose of this studywas to determine the effect and get the best combination of treatmentsfrom the propoetion of bidara fruit and red dragon fruit peel and theconcentration of E. cottonii seaweed on the characteristics of fruitleather. This study used a completely randomized design (CRD)factorial pattern of 2 factors, namely the proportion of bidara fruit andred dragon fruit peel (65%:35%; 70%:30%; 75%:25%) and theconcentration of seaweed E. cottonii (0 %; 0.4%; 0.8%; 1.2%) with 2replications. The data obtained was analysis by ANOVA, if thetreatment that had a significant effect was carried out further testingusing the DMRT test. The results showed the best treatment onproportion 65% of bidara fruit and 35% of red dragon fruit peel and1.2% concentration of seaweed, its produced fruit leather withmoisture content of 15.68%; antioxidant activity of 31.80%; vitamin Clevels of 30.78 mg/100 g; anthocyanin of 3.30 mg/100 g; tensilestrength of 1.4130 N; color includes L* of 42.98, a* of 41.26, b* of18.06; organoleptic scoring test includes taste of 3.16 (slightly soursweet), color of 4.92 (red), texture of 2.36 (not soft); and dietary fiberlevels of 4.06%